2020
DOI: 10.1111/ceo.13818
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in inner retinal function in glaucoma with nicotinamide (vitamin B3) supplementation: A crossover randomized clinical trial

Abstract: Importance: Retinal ganglion cells endure significant metabolic stress in glaucoma but maintain capacity to recover function. Nicotinamide, a precursor of NAD + , is low in serum of glaucoma patients and its supplementation provides robust protection of retinal ganglion cells in preclinical models. However, the potential of nicotinamide in human glaucoma is unknown. Background: To examine the effects of nicotinamide on inner retinal function in glaucoma, in participants receiving concurrent glaucoma therapy. D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 49 publications
4
99
2
1
Order By: Relevance
“…One explanation could be that mitochondrial dysfunction does not play a role in the pathology of glaucoma. This reasoning is very unlikely, given the accumulated evidence on the role of mitochondria in glaucoma [9,[11][12][13][14][15][16][43][44][45][46][47][48]. Alternatively, an explanation could be that GDF-15 is not a suitable biomarker.…”
Section: Plasma Gdf-15 Is Not Elevated In Oagmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation could be that mitochondrial dysfunction does not play a role in the pathology of glaucoma. This reasoning is very unlikely, given the accumulated evidence on the role of mitochondria in glaucoma [9,[11][12][13][14][15][16][43][44][45][46][47][48]. Alternatively, an explanation could be that GDF-15 is not a suitable biomarker.…”
Section: Plasma Gdf-15 Is Not Elevated In Oagmentioning
confidence: 99%
“…Strikingly, bolstering mitochondrial function by administration of nicotinamide (the amide of vitamin B3), robustly protected the mice from glaucoma. Very recent results of a clinical trial suggest that OAG patients can also benefit from this therapeutic strategy, as supplementation of nicotinamide improves their inner retinal function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…NAD + levels also decrease in models of glaucoma, suggesting that NAD + is critical to RGC health [ 18 , 19 ]. Treatment with nicotinamide (NAM), a precursor of NAD + , increases circulating NAD + and is protective in models of RGC degeneration [ 18 , 20 , 21 , 22 ] and is being tested in a glaucoma clinical trial [ 23 ]. The maximal efficacy in models was achieved only at doses that, by human equivalent dose (HED), may be above a good safety profile, and was not protective in a significant portion of the treated cohorts [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from DBA/2J mice demonstrated that oral administration of niacin reduced RGC death [79] and the therapeutic role of niacin in glaucoma was supported by studies of NTG patients indicating that there was a reduced level of dietary niacin intake in NTG patients [80]. Recent clinical trials demonstrated that supplementation with niacin improved inner retinal function in glaucoma patients [81], and the long-term effects of niacin supplementation are under investigation at present.…”
Section: Effects Of Dietary Intake Of Antioxidants In Glaucoma Patientsmentioning
confidence: 99%